Application Design for Complaints and Repairs to the Web Based Information Technology Department - Ahmad Kholilun; Kiki Ameliza (STMIK Amik Riau, 2021)
Inhil Sarimas Kelapa (PT. ISK) is a company engaged in the coconut processing industry, and the company is located in Sungai Gantang Village, Kempas District, Indragiri Hilir Regency, Riau. The company has 28 departments with various main tasks to support the company's activities in achieving the goals set. All departments use IT equipment such as software and hardware, so there is often damage to equipment that requires repairs from the IT department. Currently to make a complaint and repair problems at PT. Inhil Sarimas Kelapa still uses the manual system by filling out forms on paper, and the form is delivered to the IT department for processing. The complaint process is very ineffective and inefficient because it takes a long time. As a solution to these problems, a web-based complaint and repair complaint application is designed to make it easier for employees to do their jobs. Software that is used to create complaints applications includes Xampp, Notepad ++, Hypertext Processor and MySql. The results to be achieved are to facilitate and assist employees in reporting complaints and provide alternative solutions to the problems encountered.